Las estrategias metodológicas para desarrollar la coordinación psicomotriz de los alumnos del tercer y cuarto año de educación general básica de la escuela Miguel Riofrío de la ciudad de Loja, período 2013- 2014”. Propuesta alternativa - Calderón Vera, Freddy Fernando (2015)
The present research is focused to meet "The methodological strategies to develop the psychomotor coordination of students in the third and fourth years of basic education school Miguel Riofrio city of Loja, period 2013 -. 2014" starts to from the problem situation detected marked on the object that is given by the approaches for development of psychomotor coordination, these factors have a significant role in the psychomotor development of students when unwrapping their coordinative and intellectual capacities event. The objective is aimed at designing a model of methodological strategies adapted to generate in students and seniors better basic psychomotor development of their capacity. For best results we designed a comprehensive research hypothesis that adequate methods and techniques were used, leading to the conclusion that the non-application of appropriate methodological strategies affects insufficient development of psychomotor coordination of students